Growth and Structure of Human Populations : A Mathematical Investigation - Coale, Ansley J. (Book collections on Project MUSE., 1972)
Although mathematical demography has traditionally studied the so-called stable population (fixed mortality and fertility schedules), Ansley Coale investigates now the dynamics of population growth and structure-the changing age composition of a population as birth and death rates fluctuate. Originally published in 1972. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while p.